An Evaluation Model for Sustainable Hotel Buildings: A Case of Northern Cyprus - Mousavi, Soad Abokhamis (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
While hotel buildings exist throughout the world in diverse forms to serve travelers’ needs, their pervasive existence can also serve the environment and local communities through sustainable design. As structures representative of local culture and designed to impress visitors, hotel buildings possess the potential to influence and inspire broad dissemination of sustainable building practices and their benefits. This study aimed to develop an evaluation model for sustainable hotel buildings (EMSHB). As an adaptable model for different countries and regions according to local conditions and priorities, the EMSHB serves as a guideline to decision makers in defining the characteristics most suitable for local, sustainable hotel design. The foundational method of this study is the synthesis of sustainable building assessment criteria, such as Leadership in Energy and Environmental Design (LEED) and other sustainability measurement tools developed for buildings. To serve this purpose, various methods of measuring sustainability, sustainability indicators, and criteria of certificates for sustainability were studied. The resulting EMSHB can be used to measure sustainability among the environmental, economic, and socio-cultural aspects of hotel buildings at the first stages of design, during new construction, and in the midst of renovations of existing buildings. Upon developing the EMSHB as a globally-applicable evaluation model, this research further proposed adaptation of the model according to the local conditions and priorities of the selected context. For more reliable and comprehensive results, this study employed a mixed-methods approach incorporating both qualitative and quantitative forms of data. The qualitative method was developed based on interviews with and observations from various stakeholders, while the quantitative method was adopted from the LEED system. With the parameters of the EMSHB in mind, a localized version of the model (Local-EMSHB) was applied to one hotel building as a case study. The selected hotel was investigated in order to analyze and test the effectiveness of the method. The results of the study suggest that to have a more sustainable hotel building in the selected context, the hotel building should be evaluated based on the localized model rather than the generalized EMSHB. Defining sustainability standards according to local conditions and priorities achieved more sustainable results in hotel buildings. More broadly, the localized evaluation model can help the tourism sector and hotel industry of different countries promote sustainable development via consideration of the socio-cultural aspects, as well as environmental and economic aspects. Ultimately, application of the Local-EMSHB can help the local community achieve better quality of life. Keywords: Sustainability, Sustainable Development, Tourism Sector, Measurement of Sustainability, Sustainable Hotel Buildings.

ÖZ: Bu çalışmada, sürdürülebilir otel binası modelini irdeleme ve geliştirme amaçlanmaktadır (EMSHB). Bunun yanında, söz konusu çalışma, farklı ülke ve bölgelerdeki otel binalarının en elverişli durumlarını tanımlamada ve sürdürülebilirlik seviyesini ölçmede yardımcı olacaktır. Bu araştırma içinde bilgi toplama yöntemi olarak, Enerji ve Bina Tasarımında Liderlik (LEED) ve benzeri ölçme metotlarının esas alınıp, evrensel sürdürülebilir bina değerlendirme kriterlerinin sentezinin yapılması olarak belirlenmiştir. Bu sentez ışığında, elde edilen veriler Kuzey Kıbrıs örneği için yerelleştirilip değerlendirilecektir. Bu bağlamda, bu araştırma evrensel değerlendirme modeli oluşturmayı ve oluşturulan modelin çalışma alanı olarak seçilen Kuzey Kıbrıs için yerelleştirilerek değerlendirilmesi hedeflenmektedir. Geliştirilecek olan model, yeni otel binalarının tasarım ve inşa aşamalarında veya mevcut binaların yenileme aşamalarında, çevresel, ekonomik ve sosyokültürel nitelikleri ışığında sürdürülebilirliklerini ölçmede kullanılabilecektir. Bu hedefe ulaşabilmek için birçok sürdürülebilirliği ölçme metodu, sürdürebilirlik ilkeleri ve evrensel ölçekteki sürdürülebilirlik sertifika nitelikleri incelenmiştir. Bu inceleme, EMSHB’nin geliştirilmesi için temel oluşturmuştur. Bu bakımdan, Kuzey Kıbrıs örneği için yerelleştirilen metodun, durum ve önceliklerini anlamak için seçilen bir otel binası, en uygun metodu analiz etmek ve sürdürülebilirliğini ölçmek amacıyla incelenmiştir. Bu çalışma sonucunda, Kuzey Kıbrıs bağlamında, en sürdürülebilir otel binası tasarımı için geliştirilen “Yerel-EMSHB” metodunu takip etmesi önerilmektedir. Ek olarak, çevresel, ekonomik ve sosyokültürel faktörleri esas alınıp geliştirilen sürdürülebilir gelişim modelinin, farklı ülkelerin turizm sektörüne ve otel endüstrisine de yardım edebileceği öngörülmüştür. Aynı zamanda, yerel halkın birçok açıdan daha iyi yaşam şartlarına sahip olabilmesine olanak sağlayabileceği de saptanmıştır. Anahtar Kelimeler: Sürdürülebilirlik; Sürdürülebilir Gelişim, Turizm Sektörü; Sürdürülebilirliği Ölçme, Sürdürülebilir Otel
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2018. Supervisor: Assist. Prof. Dr. Ercan Hoşkara.
Keywords: Architecture; Hotels--Architecture--Cyprus, North; Sustainability; Sustainable Development; Tourism Sector; Measurement of Sustainability; Sustainable Hotel Buildings